Peran Penyuluhan Bimbingan Masyarakat Islam KUA Kecamatan Pattallasang terhadap Tingkat Kesadaran Beragama Masyarakat Kecamatan Pattallasang - Rimbawan, Israh Dwi; Nasir, Fahmi Ratul Ihram; Aulia A, Muhajir; Akbar, Muh Farhan; Lestari, Indah; Jihad, Afdal; Farid, Muh (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The role of Islamic religious counseling conducted by the Religious Affairs Office (KUA) in Pattallasang District is crucial in increasing the religious awareness of the local community. This study aims to analyze the effectiveness of religious guidance and counseling provided by KUA in shaping religious understanding and practices among the people of Pattallasang District. Using a qualitative approach, this research collects data through literature review and descriptive analysis. The results indicate that Islamic religious counseling significantly contributes to improving religious consciousness by providing a better understanding of Islamic teachings, reinforcing moral values, and encouraging religious practices in daily life. The study also identifies several challenges, including limited human resources and community participation constraints. However, the involvement of religious leaders and the use of digital platforms have been found to enhance the effectiveness of religious counseling. The study concludes that strengthening the role of religious counseling is essential in fostering a more religiously aware society.